Social capital and its role in sustainable dryland agricultural development case study in West Kupang subdistrict - Kupang regency - Abdurrahman, Mustafa; Suek, Johanna (Edelweiss Applied Science and Technology, 2024)
The Sustainable Dryland Agricultural Development (SDAD) in this study of socio-cultural aspects aims to understand: (1) the application of its main principles in the Kupang Barat sub-district, (2) to identify social elements that have the potential to become social capital in SDAD, and (3) its role in supporting PPKLB. The research that uses a qualitative approach with a case study strategy purposively selects 40% of the total number of villages as the observation object. In addition to farmers whose lands are designated as research subjects, there are also several key informants selected for in-depth interviews. Data analysis was conducted using the interactive model by Miles and Huberman. (1992). The results of this research conclude that (1) the agricultural conditions of PLKB in this area are categorized as "Advanced Agriculture," characterized by the application of SDAD principles that are quite good; (2) there are several elements within the structure that can be identified as social capital, namely: (a) social relationships within the kinship system according to the patterns regulated by the existing ethnic groups in the village; (b) community leaders; (c) land institutions; (d) farmer groups, as well as other social and economic groups; (e) patterns of cooperation and mutual assistance in various agricultural production activities for development; (3) these forms of social capital have significant potential roles and are interconnected to support SDAD programs in the West Kupang region.